Notas sobre la clase social en “El sueño del pongo” de José María Arguedas - Mancosu, Paola (2019)
The social sciences and literature have been in permanent dialogue, for various issues, thus both have dealt with the complex issues of social classes or the caste system that was studied and systematized by the social sciences and represented in literature: novels, stories , oral tradition. The person who articulated these two fields was José María Arguedas, who thanks to the publication of his anthropological work allows comparative studies between both fields. In this sense, this article proposes to analyze the story ““Pongoq mosqiynin / El Sueño del Pongo” through a comparison between his anthropological work and the story, with this the intervention of Arguedas in the complex relations between race and class will be observed.